Influence of Product Placements in Films and Television on consumers Brand Awareness - Kumar, Sunita (Archives of Business Research, 2017)
Today marketers are hugely making use of product placements in films and television. Product placements are being thought to be more beneficial as they are incorporated in the storyline and therefore this is hard to be missed by the viewers. The objective of the research is to find the reason for people to connect to products, their attitude towards product placements and how this attitude influences their brand awareness and buying. There have been studies before showing why marketers and consumers are preferring product placements over commercial advertisements however this study focusses on the effect of product placements on consumer brand awareness. The data for this research has been collected by a questionnaire that includes questions on general opinion as well as the influence of product placements on Brand awareness. The data has been analyzed using Advance Analytics Methods (Random Forest and Association Analysis). The former method helped in identifying the important factors and later method helped to see the various combination of factors influencing product placements in films and television.